USING PHONETIC TRANSCRIPTION TO ENHANCE STUDENTS' PRONUNCIATION OF ENGLISH VOWELS AT SMA NEGERI 6 JENEPONTO - Zela; Jumiaty, Andi Asri; Setiadi, Muhammad Asrianto (FKIP Unismuh Makassar, 2025)
This study aimed to improve students' pronunciation skills, specifically vowel sounds, through the use of phonetic transcription. A pre-experimental method was implemented, involving 25 eleventh-grade students at SMA Negeri 6 Jeneponto. The treatment consisted of structured pronunciation lessons using phonetic transcription as the primary instructional tool. The pre- test and post-test assessments included 20 vowel sounds, measured to evaluate students' progress. The results demonstrated a significant improvement in students’ vowel pronunciation, with mean scores increasing from 46.32 in the pre-test to 77.16 in the post- test. The paired samples t-test yielded a significance value of 0.000, confirming the effectiveness of phonetic transcription in enhancing students' pronunciation accuracy. Based on these findings, the alternative hypothesis (H1) was accepted, indicating that phonetic transcription significantly contributed to improving students' pronunciation of vowel sounds. This research concluded that phonetic transcription is a valuable and effective approach for addressing vowel pronunciation difficulties in English language learning. Therefore, it is recommended that educators integrate phonetic transcription into their teaching strategies to enhance students’ pronunciation and overall communication skills.